Stojan Janković in the Morean War or of Uskoks, Slaves and Subjects - Roksandić, Drago (2000)
Dealing mainly with Stojan Janković, famous Morlacchi vojvoda, this article offers a microhistorical insight into the 18th century Morlacchi society on the Triplex Cofninium with all its ambivalences and shared loyalties.
Projekt MZOS
ENG